Gastrointestinal Stromal Tumours: Etiology, Pathology and Clinical Management - Martin E Blackstein; Pierre Dubé; Jonathan A Fletcher; Oliver R Keller; Margaret Knowling; Richard Létourneau; Donald Morris; Robert Riddell; Stewart Rorke; Carol J Swallow; Canadian Advisory Committee on GIST (Canadian Journal of Gastroenterology)
Investigation of the regulation of cell growth, differentiation and death by signalling pathways has led to a greater understanding of how alterations in these pathways play a critical role in the development of some cancers, and has opened new opportunities for their treatment. In the present review, results with the prototype drug of this class, imatinib (Gleevec, Glivec [formerly STI571]; Novartis, Switzerland), in metastatic gastrointestinal stromal tumours are presented. The present review originated from a conference of the authors held in Montreal, Quebec in June 2003, under the sponsorship of Novartis.